Základní škola - Čermák, Radek (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Předmětem diplomové práce je projektová dokumentace pro provedení stavby základní školy pro první stupeň v obci Němčany. Základní škola je situována v centru obce v zastavitelném území na parcele číslo 67/2. Jedná se o třípodlažní železobetonový objekt zakončený plochou střechou z asfaltových pásů. Ve škole se nachází pět kmenových učeben pro celkem sto žáků včetně zázemí pro výdej a konzumaci jídel, kabinet pro učitele a ředitelna. Základy tvoří kombinace monolitických základových pasů a patek ze železobetonu. Budova je zateplena kontaktním zateplovacím systémem ETICS za použití desek z minerální vaty a omítnuta fasádní omítkou.

The subject of this master’s thesis is a construction project documentation for the first level of the primary school in Němčany. The primary school is situated in the centre of the village in a buildable area with a parcel number 67/2. It is a three-story building of reinforced concrete, finished with a flat roof made of asphalt strips. In the school, there are five tribal classrooms for one hundred students, including facilities for serving and consumption of meals, a teacher’s room, and a principal’s office. Foundations are constructed from a combination of monolithic strips and reinforced concrete footings. The building is insulated with an ETICS system using mineral wool boards and facade plaster.
Elementary School
Keywords: Základní škola; novostavba; řadová zástavba; plochá střecha; železobetonová monolitická konstrukce; Primary school; new building; row building; flat roof; reinforced concrete monolithic construction